Streetlight intelligent remote control system based on wireless communication - Hernandez-Jayo, U.; Angulo, I.; Elejoste, M. P.; Perallos, A.; Chertudi, A.; Moreno, A. (2013 10th International Conference on Remote Engineering and Virtual Instrumentation (REV), 2013)
This paper presents a streetlight remote management system, based on wireless communication technologies, which will provide tangible solutions to improve energy efficiency by adapting to the changes in the contextual needs. The proposed solution is said to be intelligent since light dimming is fixed based on the analysis of the data provided by the deployed sensors.